2000
DOI: 10.1080/14634980008650681
|View full text |Cite
|
Sign up to set email alerts
|

Integration of varying responses of different organisms to water and sediment quality at sites impacted and not impacted by the petroleum industry

Abstract: The toxicity of surface waters and interstitial waters from sediments were determined at six study sites in Todos as Santos Bay, Bahia, Brazil, to evaluate the possibility of chronic environmental impact induced by 40 years of exposure to the local petroleum industry. Samples collected from four sites associated with the extraction, transportation and refinement of petroleum, and from two control sites, were tested at seven three-month intervals. Toxicological assays using acute mortality of brine shrimp (Arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Previous studies in the Bay of Todos os Santos (Nascimento, 1996;Tavares, 1996;da Silva et al, 1997;Nascimento et al, 1998bNascimento et al, , 2000a identified a moderate to low pollution potential in all areas of the petroleum industry, except for the refinery site, where the sediment toxicity was classified as high (Nascimento et al, 1998a(Nascimento et al, , 2000a.…”
Section: Article In Pressmentioning
confidence: 97%
“…Previous studies in the Bay of Todos os Santos (Nascimento, 1996;Tavares, 1996;da Silva et al, 1997;Nascimento et al, 1998bNascimento et al, , 2000a identified a moderate to low pollution potential in all areas of the petroleum industry, except for the refinery site, where the sediment toxicity was classified as high (Nascimento et al, 1998a(Nascimento et al, , 2000a.…”
Section: Article In Pressmentioning
confidence: 97%
“…However, larvae of various sea urchin species have been previously used to test the quality of waters and to provide data to estimate and prevent environmental harmful effects of effluents and products to be released in coastal areas [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Such toxicity tests conducted for known concentrations of several contaminants (mostly metals, hydrocarbons and pesticides) have recently been developed in tropical and subtropical regions to identify suitable target-species and establish related benchmarks, a necessary step to define bioassays suitable for ecological risk assessments (Peters et al 1997). However, very few works involving in situ bioassays or laboratory exposure to field-collected seawater or sediment samples have been conducted to date in coastal tropical and subtropical waters (Rumbold and Snedeker 1999;Nascimento et al 2000).…”
Section: Bioassaysmentioning
confidence: 99%